2015
DOI: 10.1007/s00198-015-3108-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia and osteoporosis: reappraisal of a novel association

Abstract: Summary Age was a modifier of the independent association between hyponatremia and osteoporosis (OP). Risk of OP was the highest in the youngest age group as compared to older patients. A longer duration of hyponatremia revealed a similar association with OP in all anatomical sites. Introduction Epidemiologic studies provide conflicting results on the relationship between hyponatremia and OP. Our aim is to test the modification effect of age on the relationship between hyponatremia and OP at various anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…A study of single serum Na ϩ values 14 days before or after imaging suggested a modest dose-response between increasing serum Na ϩ and increasing total hip bone mineral content, BMD, and T-score (20). A recent study of dual-energy x-ray absorptiometry data from patients who had at least one hyponatremic interval in the 2 years prior to densitometry suggested that more severe and longer duration hyponatremia was associated with highest risk of osteoporosis in younger patients (21). The present study provides further evidence that the association between hyponatremia and osteoporosis is dose dependent (more severe hyponatremia results in higher elevated risk) and time dependent (chronic hyponatremia results carries higher risk than prior hyponatremia alone).…”
Section: Discussionmentioning
confidence: 95%
“…A study of single serum Na ϩ values 14 days before or after imaging suggested a modest dose-response between increasing serum Na ϩ and increasing total hip bone mineral content, BMD, and T-score (20). A recent study of dual-energy x-ray absorptiometry data from patients who had at least one hyponatremic interval in the 2 years prior to densitometry suggested that more severe and longer duration hyponatremia was associated with highest risk of osteoporosis in younger patients (21). The present study provides further evidence that the association between hyponatremia and osteoporosis is dose dependent (more severe hyponatremia results in higher elevated risk) and time dependent (chronic hyponatremia results carries higher risk than prior hyponatremia alone).…”
Section: Discussionmentioning
confidence: 95%
“…Other study conducted in the University of Michigan showed that hip osteoporosis occurred in 17.6 % of patients with HN as compared to 6.6 % of patients with normal serum sodium level, but osteoporosis was higher in younger age group (less than 55 years) as compared to older adults [13]. Considering different results in previous studies which may be due to the region where study participants were living and different underlying conditions; outcome variables which have been measured in the study protocol; and cut-off points of serum sodium concentration for determination of HN, this research has been proposed to assess the association of HN with bone density and falls in older population of Amirkola, Northern Iran.…”
Section: Introductionmentioning
confidence: 83%
“…Nearly, one third of body sodium is stored in the bone [25]. The association of HN with balance impairment, falls and bone fractures in the elderly can be justified by different mechanisms including increase unsteady gait related to cognitive impairment; bone resorption and its fragility [1,7,8,25], furthermore, another research presented that the sustained low extracellular sodium ion concentrations could directly stimulate osteoclastogenesis and that hyponatremia-induced oxidative stress might be involved in the mechanism [26].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental and clinical evidence have indicated in recent years that hyponatremia may negatively affect bone health [5,6,[8][9][10][11][12][15][16][17]. This study focused on the comprehension of the mechanisms leading to bone frailty in the presence of reduced [Na ? ]…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the risk of osteoporosis appeared to be higher in hyponatremic patients aged less than 55 years, suggesting that chronic hyponatremia may translate early aging of bone in young individuals. [16].…”
Section: Introductionmentioning
confidence: 95%